Deterministic positioning and alignment of a single-molecule exciton in plasmonic nanodimer for strong coupling - Renming Liu; Ming Geng; Jindong Ai; Xinyi Fan; Zhixiang Liu; Yu-Wei Lu; Yanmin Kuang; Jing-Feng Liu; Lijun Guo; Lin Wu (Nature Communications, 2024)
Abstract Experimental realization of strong coupling between a single exciton and plasmons remains challenging as it requires deterministic positioning of the single exciton and alignment of its dipole moment with the plasmonic fields. This study aims to combine the host–guest chemistry approach with the cucurbit[7]uril-mediated active self-assembly to precisely integrate a single methylene blue molecule in an Au nanodimer at the deterministic position (gap center of the nanodimer) with the maximum electric field (EFmax) and perfectly align its transition dipole moment with the EFmax, yielding a large spectral Rabi splitting of 116 meV for a single-molecule exciton—matching the analytical model and numerical simulations. Statistical analysis of vibrational spectroscopy and dark-field scattering spectra confirm the realization of the single exciton strong coupling at room temperature. Our work may suggest an approach for achieving the strong coupling between a deterministic single exciton and plasmons, contributing to the development of room-temperature single-qubit quantum devices.